A Variant of Leptin Gene Decreases the Risk of Gastric Cancer in Chinese Individuals: Evidence from a Case–Control Study [Corrigendum] - Ma R; He Q (Dove Medical Press, 2020)
Ma R, He Q. Pharmgenomics Pers Med. 2020;13:397–404. The authors have advised the affiliation list on page 397 is incorrect. The correct author list and affiliation is as follows. Renjie Ma1Qi He21Department of General Surgery, The People’s Hospital of Danyang, Affiliated Danyang Hospital of Nantong University, Danyang, 212300, Jiangsu Province, China; 2Department of Infectious Disease, The People’s Hospital of Danyang, Affiliated Danyang Hospital of Nantong University, Danyang, 212300, Jiangsu Province, China Read the original article